Preparation and application of enzyme-based hydrogels - Wen, Yahui; Wang, Xinghai; Zhao, Jinxue; Zhai, Xuejing; Xia, Wei; Li, Peiyi; Lai, Keqiang; Wu, Lidong (Biosensors and bioelectronics. X, 2025)
Enzymes are highly efficient catalysts in nature, governing countless reactions in biological systems. Enzyme-based hydrogels are three-dimensional network materials with enzyme activity, created by loading enzymes into hydrogels or using hydrogels to synthesize polymeric materials. Due to their high biocompatibility, enzyme-based hydrogels exhibit broad application potential in various fields. In recent years, researchers have been continuously exploring new preparation methods to improve the physical, chemical, and biological properties of enzyme-based hydrogels. Additionally, the introduction of materials such as graphene, carbon nanotubes, and metal-organic frameworks (MOFs) has further enhanced the biological activity of these hydrogels. This review summarizes recent preparation methods and structural characteristics of enzyme-based hydrogels, with a focus on their applications in biosensors and medical fields, highlighting the vast application prospects of enzyme-based hydrogels. •Enzymes play a pivotal role as catalysts in biological reactions, yet their fragile structure makes it difficult to incorporate them into synthetic materials.•Hydrogels provide a suitable environment for enzymes, and some hydrogels themselves exhibit enzymatic activity.•Preparation methods for introducing enzymes into hydrogels while maintaining enzyme activity.•Applications of enzyme-loaded hydrogels and enzyme-mimetic hydrogels.